The Isolation and Construction of an Infectious Clone for a Duck Adenovirus Type 3 Strain - Haipeng Lu; Mei Tang; Zhifei Zhang; Mi Wu; Chunxiu Yuan; Xue Pan; Qinfang Liu; Qiaoyang Teng; Bangfeng Xu; Minghao Yan; Dawei Yan; Fenglong Wang; et al. (Microorganisms)
A duck adenovirus type 3 strain, SD2019, was isolated from sick Muscovy ducks in our laboratory in 2019. To study the biological properties of the virus, an infectious clone of the SD2019 strain was successfully established. The plasmid containing the whole genome of DAdV-3 was digested with Pac I and the linearized DNAs were electortransfected into LMH cells; the cells showed cytopathic effects (CPEs) at 96 h post transfection and the rescued virus (rSD2019) was identified by PCR and indirect immunofluorescence assays (IFAs). The biological characteristics of strain rSD2019 were studied in vitro and in vivo and the results show that rSD2019 grew to similar titers as compared with the wild-type SD2019 strain in LMH cells, as well as showing similar replication and virulence in Muscovy ducks. The establishment of a reliable reverse genetics system for DAdV-3 provides a foundation for future studies of DAdV-3.